Predicting MoM Error Currents by Inverse Application of Residual E-Fields - Fourie, Andre P. C. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents a methodology to predict a posterori the error associated with a Method-of-Moments solution. The discussion is limited to a one dimensional pulse basis function wire-based implementation, but is easily extended. A Formulation for Error Prediction based on the relationship between the error in the boundary conditions and the error in the solution is presented, and validated by an over-segmented problem. The formulation is then used in a normally-segmented solution to predict the error by means of a linear interpolation of the calculated current which results in a smoother boundary condition error. The results show that this normally-segmented methodology predicts the error current within 5% of the "accurate" error current obtained by a 20:1 oversegmentation of the problem. Further work needs to be performed to extend this to the multidimensional case, although no technical difficulties are expected with this.